I depositi Del Pleistocene inferiore della Bassa val Di Cecina (Toscana, Italia): ricostruzione stratigrafico-deposizionale e proposta di suddivisione in unità allostratigrafiche - SARTI, GIOVANNI; Ciampalini A.; Consoloni I.; Cerrina Feroni A. (2007)
In the area comprised between the villages of Riparbella and Casale Marittimo (lower Cecina Valley, Tuscany, Italy) a large amount of Pleistocene deposits outcrops. Through a detailed geological survey integrated with facies analysis five litostratigraphic units, grouped in three Allostratigraphic Units (UA), have been detected. The oldest (UA7), lower pleistocenic in age, is formed by two litostratigraphic units (“Conglomerati delle Ginepraie” and “Sabbie ed argille ad Arctica islandica”) showing latero-vertical relationships and are organized in a transgressive-regressive cycle. The “Conglomerati delle Ginepraie” are arranged in a fining upwards trend and were deposited in small coalescent deltaic environments. Three depositional facies are recognized within the “Sabbie ed argille ad Arctica islandica” recording a fining-coarsening and deepening shallowing upward trend. The UA7 lies in unconformity above pre-quaternary deposits. The second (UA6), lower pleistocenic in age, is also constituted by two heteropic and transgressive litostratigraphic units (“Conglomerati delle Lame” and “Arenarie e Sabbie di Montescudaio”) lying in angular unconformity on the UA7. The “Conglomerati delle Lame”, showing a well developed imbrication, were deposited in a foreshore to upper shoreface depositional environment. The “Arenarie e Sabbie di Montescudaio” are characterized by a high to low planar-cross stratification and sometimes by overturned stratification and were deposited in a shallow marine environment. The regressive phase of this UA is not preserved due to erosive processes. The youngest unit (UA4, “Conglomerati di Serra all’Olio”), was instead deposited in fluvial-braided environment and lies in angular unconformity on the others UA. The middle pleistocenic age of this unit has been inferred on the basis of its stratigraphic position. This stratigraphic reconstruction strongly conflict from previous interpretations. Important climatic and geological remarks derive from the finding of two taxa (Arctica islandica and ...